The Analysis of Students Critical Thinking using the Junior High School Student Online Module - Mulyono; Wahono Widodo; Suyono (IJORER : International Journal of Recent Educational Research, 2021)
This study aims to describe the results of the feasibility of the learning tools applied in class VII SMP based on the validator's assessment, test results and student responses. In research with a quantitative approach and the learning device development model used is Research and Development (R and D). The data collection method used critical thinking skills tests in the form of pretest and posttest, observation sheets, and student response questionnaires to the development of online modules. In line with the objectives of the research, the results showed that the validation results were valid and reliable so that the learning devices were declared suitable for use. The results of the observation of students' critical thinking skills showed very good, and the results of the N-gain showed that the medium category was 15 students, the high category was 5 students, and the student response questionnaire to the online module was 92.50% with a very good category. SPPS test shows that online module gives influence for critical thinking students. All of teachers can use the online module for many learning model to increase critical thinking students.